2020
DOI: 10.1186/s12886-020-01349-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of posterior capsule opacification of the Alcon Clareon IOL vs the Alcon Acrysof IOL using a human capsular bag model

Abstract: Background: Posterior capsule opacification (PCO) after cataract surgery is influenced by intraocular lens (IOL) design and material. The following is an ex vivo comparison of PCO between the Clareon vs. the AcrySof IOL in human capsular bags. Methods: Twenty cadaver capsular bags from 10 human donors were used, with the novel hydrophobic IOL (Clareon, CNA0T0) being implanted in one eye and the other eye of the same donor receiving the AcrySof IOL (SN60WF) following phacoemulsification cataract surgery. Five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…11 A recent study using human capsular bag model reported similar PCO formation rates with AcrySof and Clareon IOLs. 25 In this study, PCO was not assessed at the end of the cataract surgery. The rate of PCO reported in this study was 5.4% (19/350), and the rate of Nd:YAG capsulotomy was 4.6% (16/350).…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent study using human capsular bag model reported similar PCO formation rates with AcrySof and Clareon IOLs. 25 In this study, PCO was not assessed at the end of the cataract surgery. The rate of PCO reported in this study was 5.4% (19/350), and the rate of Nd:YAG capsulotomy was 4.6% (16/350).…”
Section: Discussionmentioning
confidence: 99%
“…The ciliary body is pinned to the ring and the capsular bag suspended over the lumen. This approach combined with improvements in culture conditions that better reflect surgical inflammation, maintains the capsular bag integrity and is ideal for studying IOLs in relation to PCO (Eldred et al, 2014;Eldred et al, 2019;Hillenmayer et al, 2020) (Figure 2).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…• Inhibition of molecular pathways [112,121,132,134,135] • Investigation of molecular pathways [29,136] • Investigation of intraocular lenses [108,137,138] Clinical studies n/a…”
Section: Model Type Tissue Donors Application Referencesmentioning
confidence: 99%